1977
DOI: 10.1111/j.1365-2133.1977.tb15060.x
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine and tryptamine pathways in scleroderma

Abstract: Levels of 5-hydroxyindoleacetic acid, indoleacetic acid and total indoles were determined in the urine of 23 patients with systemic scleroderma and 7 patients with cutaneous scleroderma, before and after peroral loading with L-tryptophan (0-1 g/kg body weight). Before loading, 5-hydroxyindoleacetic acid levels were normal in nearly all cases of systemic scleroderma as well as of cutaneous scleroderma; however after loading, in nearly one half of cases there was no normal increase of this metabolite. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…It has been suggested that those affected might metabolize tryptophan along an alternative metabolic pathway, leading to accumulation of toxic metabolites such as kynurenine [75]. Disorders of amine metabolism have also been implicated in the pathophysiology of scleroderma [76].…”
Section: Toxic Oil Tryptophan and Sclerodermamentioning
confidence: 99%
“…It has been suggested that those affected might metabolize tryptophan along an alternative metabolic pathway, leading to accumulation of toxic metabolites such as kynurenine [75]. Disorders of amine metabolism have also been implicated in the pathophysiology of scleroderma [76].…”
Section: Toxic Oil Tryptophan and Sclerodermamentioning
confidence: 99%
“…Serotonin has induced dermal fibrosis in rats 11 and can stimulate DNA synthesis in fibroblasts in vitro 12 . In one study, abnormal tryptophan and serotonin metabolism was demonstrated in patients with idiopathic scleroderma and systemic sclerosis 13 . Serotonin has recently been demonstrated to induce proliferation of cardiac valvular subendocardial cells in vitro , 14 suggesting that the fibrotic process affecting skin and cardiac tissue may have a shared mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…12 In one study, abnormal tryptophan and serotonin metabolism was demonstrated in patients with idiopathic scleroderma and systemic sclerosis. 13 Serotonin has recently been demonstrated to induce proliferation of cardiac valvular subendocardial cells in vitro, 14 suggesting that the fibrotic process affecting skin and cardiac tissue may have a shared mechanism. However, serotonin is secreted by the majority of carcinoid tumours yet carcinoidrelated scleroderma is unusual, suggesting that other factors such as genetic predisposition or other neuroendocrine mediators must play a role.…”
Section: Discussionmentioning
confidence: 99%
“…are also associated with sclerodermalike disease. Abnormalities in tryptophan metabolism have been described in patients with scleroderma and in family members of a patient with scleroderma (33,34). Perhaps, in a host with an occult enzyme deficiency, an iatrogenic excess of substrate for kyn-urenine and serotonin synthesis could have unmasked the scleroderma-like disease.…”
Section: Discussionmentioning
confidence: 99%